IMPLEMENTATION ANALYSIS SERVICES MARKETING STRATEGY ROOM (CASE ON KHARISMA HOTEL BUKITTINGGI) - Rita Saputriyani; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Service marketing strategy is a set of tools that can be used marketer, which consists of various elements of a marketing program that should be considered that the implementation of the strategy defined marketers can be successful. The purpose of this study was to megetahui implementation of marketing strategy services performed charisma bukittinggi hotel.Kharisma Hotel Bukittinggi established PT. Mega Kharisma Asia Sentosa and all operating on 10 August 2002. Hotel charisma is suattu hotels are accommodation facilities that play a role in the operation of services in the form of specialty services to the community in need, Kharisma Hotel is a 2-star hotel.The results showed that the analysis of marketing strategy services at Kharisma Hotel Bukittinggi categorized very well, indicated by respondents when distributing questionnaires.Keywords: Marketing Services